2013
DOI: 10.1371/journal.pgen.1003957
|View full text |Cite
|
Sign up to set email alerts
|

Oct4 Is Required ∼E7.5 for Proliferation in the Primitive Streak

Abstract: Oct4 is a widely recognized pluripotency factor as it maintains Embryonic Stem (ES) cells in a pluripotent state, and, in vivo, prevents the inner cell mass (ICM) in murine embryos from differentiating into trophectoderm. However, its function in somatic tissue after this developmental stage is not well characterized. Using a tamoxifen-inducible Cre recombinase and floxed alleles of Oct4, we investigated the effect of depleting Oct4 in mouse embryos between the pre-streak and headfold stages, ∼E6.0–E8.0, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 73 publications
(112 reference statements)
5
73
0
Order By: Relevance
“…S3, A and B), suggesting that Gata6 might not be the earliest marker of cells on the differentiation path. Nevertheless, our finding is consistent with the importance of Oct4 in cells of the PS region (43,66).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…S3, A and B), suggesting that Gata6 might not be the earliest marker of cells on the differentiation path. Nevertheless, our finding is consistent with the importance of Oct4 in cells of the PS region (43,66).…”
Section: Discussionsupporting
confidence: 92%
“…Both Oct4 and Gata6 have been reported to be expressed in the PS region at the gastrulation stage, in addition to their respective distribution in the EPI and VE before gastrulation (31,32,35,43,44). We inferred that Oct4 ϩ Gata6 ϩ cells could be in the PS region of the late-stage E6.5 embryos after gastrulation had begun (embryos VII-X were named E6.5_Late and their EPI was named Late EPI).…”
Section: Gata6mentioning
confidence: 99%
“…Furthermore, conditional loss-of-function experiments revealed that Oct3/4 is required for normal primitive streak development in gastrulating mouse embryos (DeVeale et al, 2013). In the late phase of reprogramming, which proceeds independently of exogenous reprogramming factor expression, the expression of endogenous OCT3/4 reaches a level similar to that of ESCs and iPSCs.…”
Section: Transient Expression Of Developmental Genes During Reprogrammentioning
confidence: 99%
“…Several studies have shown that Oct4 has explicit lineagespecifying functions (16,(29)(30)(31)(32). Initial reports revealed that ESCs expressing higher Oct4 levels induce differentiation toward the mesoendoderm lineage (33).…”
Section: Pluripotency Factors In Cell Fate Commitmentmentioning
confidence: 99%